Protective factors against suicidal ideation in spanish-speaking adolescents: a systematic review - Godoy-León, Nicole Brighet (2025)
This systematic review examines protective factors against suicidal ideation in Spanish-speaking adolescents. Its objective was to identify key protective variables through a systematic review of 11 empirical studies published between 2020 and 2024, retrieved from Web of Science, Scopus, PubMed, PsycINFO, ERIC, SciELO, and Redalyc, and meeting criteria for adolescent populations, full-text access, and article format. The analysis of published literature revealed five recurrent protectors: family support, emotional intelligence, resilience, self‑esteem, and morning school shifts. These findings suggest that interventions should strengthen family networks, cultivate emotional skills, and consider school schedule adaptations to reduce suicidal vulnerability. The creation of culturally adapted, longitudinal preventive programs is recommended to evaluate their effectiveness.